MO877: Dynamics of SARS-COV-2-Spike-Reactive Antibody and T-Cell Responses in Chronic Kidney Disease Patients Within 3 Months After Covid-19 Full Vaccination. (3rd May 2022) - Panizo Gonzalez, Nayara; Albert, Eliseo; Gimenez-Civera, Elena; Solano Rivera, Camila; Jesús Puchades Montesa, Maria; Gandia, Lorena; D'marco, Luis; Maria Pérez-Baylach, Carmen; Bonilla, Begoña; Sancho, Asunción; Gavela, Eva; Gonzalez-Rico, Miguel; et al.
Abstract: BACKGROUND AND AIMS: Little is known regarding the dynamics of antibody and T-cell responses in chronic kidney disease (CKD) following COVID-19 vaccination. METHOD: Prospective observational cohort study including 144 participants on haemodialysis (HD) ( n = 52), peritoneal dialysis (PD) ( n = 14), kidney transplantation (KT) ( n = 30) or advanced chronic kidney disease not on dialysis (ACKD), and healthy controls ( n = 18). Anti-Spike(S) antibody and T-cell responses were assessed at 15 days (15D) and 3 months (3M) after vaccination. RESULTS: Anti-S antibodies at 15D and 3M were detectable in 95% (48/50)/98% (49/50) of HD patients, 93% (13/14)/100% of PD patients, 67% (17/26)/75% (21/28) of KT patients and 96% (25/26)/100% (24/24) of ACKD patients. Rates for healthy controls were 81% (13/16)/100% (17/17). Antibody levels decreased at 3M in HD ( P = 0.04), PD ( P = 0.008) and ACKD patients ( P = 0.0009). In KT, patients levels increased ( P = 0.04) between 15D and 3M, although they were low at both time points. Detectable T-cell responses notably increased at 3M in HD patients ( P < 0.022). In PD, patients response increased by 15D (13/14; 93%) and 3M (9/9; 100%), while they were present in KT patients at 41% (12/27), 84% (22/26) and 96% (25/26) at baseline. Detectable T-cell responses in ACKD patients reached 80% (20/25) and 89% (17/19) at 15D and 3M, respectively. whereas in healthy controls it was 67% and 89% at 15D and 3M. CONCLUSION: Most HD, PD and ACKD patients develop SARS-CoV-2-S antibody responses comparable to that of healthy controls, in contrast to KT recipients. Antibody waning at 3M was faster in HD, PD, ACKD patients. No differences in SARS-CoV-2 T-cell immunity responses were noticed across study groups.